Wood Colour Test of Fisherman’s Boat on Microorganism Linkage in Kangean - Nurhatika, Sri; Nurhayati, Awik P.D. (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
Most of Indonesian fishermen have been using wooden boat. The boat has been used by fishermen in the north shore of East Java are made from Teak and Silk cotton tree. The leakage indication had not been shown on its linkage but on the boat caused by a microor-ganism called biofouling. The research used Colony For-ming Unit method (CFU) and Saburoud Dextrose Agar (SDA) as a fungus counting medium and Nutient Agar (NA) as a bacteria counting medium. Each medium had been adjusted to the microorganism. The result shows that the wood and the paint which were used to build the boat influenced the type of microorganism, fungus, and bac-teria on the boat. Bacteria preferred to stick on the yellow boat, and fungus preferred to stick on the green boat. The microorganism had been identified on the red Nyamplung tree, Kosambi tree, Jackfruit tree, Kamfer tree, and Teak tree are Micrococcus sp, Bacillus sp, and Pseudomonas sp, and all of those are bacteria. The other microorganism had been identified were Aspergillus niger, Aspergillus oryzae, Penicillium sp, Candida sp, Rhodotorulla sp, Saccharomyces sp, Verticillium sp, Paecilomyces sp, Monillia sp, and Altenaria sp, and all of those are fungus.